2019
DOI: 10.1177/2331216518821449
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus Treatment Using Noninvasive and Minimally Invasive Electric Stimulation: Experimental Design and Feasibility

Abstract: Noninvasive transcranial or minimally invasive transtympanic electric stimulation may offer a desirable treatment option for tinnitus because it can activate the deafferented auditory nerve fibers while posing little to no risk to hearing. Here, we built a flexible research interface to generate and control accurately charge-balanced current stimulation as well as a head-mounted instrument capable of holding a transtympanic electrode steady for hours. We then investigated the short-term effect of a limited set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Tinnitus reduction has been reported as a positive effect of intracochlear electrical stimulation in studies on cochlear implantation in hearing-impaired people [ 89 , 90 ]. Some of these studies demonstrated therapeutic suppression of tinnitus symptoms, but there is no consensus on the most effective type of stimulus [ 7 , 8 ]. In this systematic review, we aimed to provide a comprehensible overview of the electrical intra- and extracochlear stimulation patterns studied and their effect on tinnitus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tinnitus reduction has been reported as a positive effect of intracochlear electrical stimulation in studies on cochlear implantation in hearing-impaired people [ 89 , 90 ]. Some of these studies demonstrated therapeutic suppression of tinnitus symptoms, but there is no consensus on the most effective type of stimulus [ 7 , 8 ]. In this systematic review, we aimed to provide a comprehensible overview of the electrical intra- and extracochlear stimulation patterns studied and their effect on tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Intracochlear stimulation through a CI is already highly developed for speech recognition in deafened patients. This technology could combine electrical stimulation to optimize both speech recognition and tinnitus suppression [ 7 , 8 ]. Nevertheless, due to its invasive approach, cochlear implantation can induce residual hearing deterioration in the ear implanted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, non-invasive deep brain stimulation has not been achieved in humans. However, remote activation of the auditory nerve through tES has been shown to produce auditory sensations 26,52 , suppress the loudness of tinnitus 25,26,52,53 , and reduce the annoyance of the tinnitus 53 . Optimizing stimulation parameters with the methods introduced here, could aid the development of viable treatment or therapy options for a wide variety of neurological disorders.…”
Section: Discussionmentioning
confidence: 99%